ANSWER
The system has two solutions.
Step-by-step explanation
The given equations are
![y=-2x + 2](https://img.qammunity.org/2020/formulas/mathematics/high-school/rjqgz48w5ftq9lx23miumjihs1sf4bdd7d.png)
and
![y={x}^(2) - 3x](https://img.qammunity.org/2020/formulas/mathematics/high-school/csj4jxyjm4agw1i6yvmvr409mnj12adr77.png)
We equate both equations to obtain;
![{x}^(2) - 3x =-2x + 2](https://img.qammunity.org/2020/formulas/mathematics/high-school/5uxxgsmrpgfddmux7xy2wnyl9ryzvyr82b.png)
This implies that,
![{x}^(2) - 3x +2x - 2 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/rhv2dkfve6gxpnpmcc2e4x2klqaw72c1mh.png)
![{x}^(2) - x - 2 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/ybjjoycankl7jff0jwgg8e0mc81e1sd6av.png)
where a=1, b=-1,c=-2.
We find the discriminant, D=b²-4ac of this equation to be;
![D = {(-1)}^(2) - 4(1)( - 2) = 9](https://img.qammunity.org/2020/formulas/mathematics/high-school/qp6xpj3s5bv7xgzsgza8wjy9aj1172x7n9.png)
Since the discriminant is greater than zero, it means the two functions intersected at two distinct points.
Hence the system has two solutions.